Anatomical and micromorphological analysis of root, stem and leaf of Echinochloa crus-galli (L) Beauv. - Jovanović, Darko; Rančić, Dragana (Acta herbologica, 2025)
The aim of this research was to investigate and characterise the anatomical structure of vegetative organs in Echinochloa crus-galli (L) Beauv., commonly known as cockspur or barnyardgrass.  E. crus-galli is a member of the Poaceae family and is a common weed species which occures in many crops. For the purpose of these research, fully developed plants were collected at experimental field of the Institute of Vegetable crops in Smederevska Palanka. For anatomical investigation of root, stem and leaf several methodes of microslide preparation were employed. Cockspur has high water requirements and belongs to the hygrophilous weed species (F4), what in in the anatomical level is reflected through large intercellular spaces (aerenchyma) present in stem and root. Generally speaking, anatomical characteristics of E. crus-galli, especially considering not only lignified endodermis, but also presence of lignified exodermis in roots, shares similarities with anatomical characteristics of rice (Oryza sativa L.), in which fields this species actually represent one of the most troublesome weeds. The anatomical structure of the stem is typical for monocots, featuring a single-layered epidermis on the surface, a hypodermis composed of chlorenchyma and sclerenchyma, and collateral vascular bundles collateral vascular bundles were distributed by pattern characteristic for Poaceae family, scattered throughout the main body of the stem, surrounded by well-developed parenchyma tissue. The leaves are characterized by Kranz anatomy, which is typical for plants with C4-type photosynthesis. The leaf surface is characterized by the presence of short, non-glandular trichomes occur on both leaf surfaces, the adaxial and abaxial, while silica cells are located exclusively in the adaxial epidermis. These morpho-anatomical characteristics could be an significant factor in absorption of foliar applied herbicides, so understanding their role could be of a great importance for successful chemical control.
Keywords: cockspur, barnyardgrass, stomata, C4 plant, silica cells